ANALISIS FAKTOR EKSPLOITASI HUTAN DI IUPHHK-HA PT BINA MULTI ALAM LESTARI - Yudha Galoh Kelana Putra; Zainal Abidin; Lusyiani Lusyiani (Jurnal Sylva Scienteae, 2021)
The exploitation factor is one of the important parameters in harvesting forest products in accordance with the 0.70 quota set by the Ministry of Forestry. The method used in this study refers to several sources, in calculating the exploitation factor using a formula based on "allian" (Moeljono. S. B) as well as for the calculation of log volume. The main component in this study determines the aspects of exploitation factors and log volume with wood volume as primary data used and which is expected to be utilized from exploitation activities and secondary data as additional data to support research obtained through interviews, citing data from companies. Secondary data consisted of the general conditions of the research location, topography, field, area and location of the cutting compartments. The value of the Exploitation Factor in IUPHHK-HA at PT Bina Multi Alam Lestari from 265.95 m³ of trees cut and successfully utilized in the 211.24 m³ cutting block to log yards (logpond) did not experience a reduction or depreciation, from this result the value of the Exploitation Factor the value obtained is 0.79, the value obtained has met the quota set by the government. The yield of wood volume that can be utilized in plot E-12 with a volume value of 46.86 m³, on plot F-12 the volume value is 52.22 m³, for plot F-13 the volume value is 39.55 m³ and then plot J-14 with a value volume 72.61 m³. The average yield value of all logged plots can be utilized with an overall value of 211.24 m³.Keywords: Exploitation factor, harvesting forest products, limited production forest